Thirty-four novel mutations of the GLA gene in 121 patients with Fabry disease - Schäfer, Ellen; Baron, Karin; Widmer, Urs; Deegan, Patrick; Neumann, Hartmut P. H.; Sunder-Plassmann, Gere; Johansson, Jan-Ove; Whybra-Trümpler, Catharina; Ries, Markus; Pastores, Gregory M.; Mehta, Atul B.; Beck, Michael; et al. (Human mutation, 2005)
Fabry disease (FD) is an X-chromosomal disorder caused by mutations in the GLA gene encoding the lysosomal enzyme α-galactosidase A. We performed mutation screening on a cohort of 121 patients including 84 male and 37 female index cases and identified a total of 90 different mutations, 34 of which are reported for the first time here. Both point mutations (74.4%) and ‘short length’ rearrangements (25.6%) were found, including missense (54.4%), nonsense (14.4%), and splice site point mutations (5.6%), deletions (17.8%) or insertions/duplications (5.6%) of a few nucleotides, and complex rearrangements including larger deletions (2.2%). GLA mutations were identified in 82 (97.6%) of the 84 unrelated male patients. © 2005 Wiley-Liss, Inc.